Absorptive capacity and innovation: When is it better to cooperate? - Abiodun A. Egbetokun; Ivan Savin (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Cooperation can benefit and hurt firms at the same time. An important question then is: when is it better to cooperate. And how can an appropriate partner be selected? In this paper we present a model of inter-firm cooperation driven by cognitive distance, appropriability conditions and external knowledge. Absorptive capacity of firms develops as an outcome of the interaction between absorptive R&D and cognitive distance from voluntary and involuntary knowledge spillovers. Thus, we offer a revision of the original model by Cohen and Levinthal (1989) accounting for recent empirical findings and explicitly modeling absorptive capacity within the framework of interactive learning. We apply that to the analysis of firms' cooperation and R&D investment preferences. While the focus of this paper is limited to a static scenario, where the cognitive distance between cooperating firms is fixed and given exogenously, in Savin and Egbetokun (2012) we address the dynamic approach and provide more extensive simulation results.
Keywords: C63; D83; L14; O32; O33; 330; inter-firm cooperation; absorptive capacity; cognitive distance; innovation; knowledge spillovers; Unternehmenskooperation; Forschungskooperation; Wissenstransfer; Innovation; Kognition; Theorie